1997
DOI: 10.1177/0266242697153004
|View full text |Cite
|
Sign up to set email alerts
|

Some Research Perspectives on Entrepreneurship Education, Enterprise Education and Education for Small Business Management: A Ten-Year Literature Review

Abstract: GARY GORMAN IS AN ASSOCIATE DEAN AND associate professor and Dennis Hanlon an assistant professor at the Faculty of Business Administration, Memorial University ofNewfoundland, Canada, and Wayne King is director of the P. J. Gardiner Institute for Small Business Studies as well as an assistant professor at Memorial University of Newfoundland. This paper reviews the literature in the areas of entrepreneurship education, enterprise education and education for small business management. The review covers the peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
545
0
37

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 798 publications
(621 citation statements)
references
References 1 publication
11
545
0
37
Order By: Relevance
“…Le principal obstacle se situe cependant, à l'instar des notions d'entrepreneuriat et de « culture entrepreneuriale », au niveau de la difficulté de définir les termes utilisés pour parler d'entrepreneuriat en milieu scolaire. Dans les écrits anglophones, ce vocabulaire se cristallise autour de deux principaux vocables, à savoir entrepreneurship education et enterprise education, auxquels on pourrait ajouter un troisième, soit small business education (Breen, 2004;Gorman, Hanlon & King, 1997). Si ces termes peuvent parfois être utilisés de manière interchangeable, nombre d'auteurs mettent pourtant en évidence la spécificité de chacun d'eux (Cummins & Dallat, 2004;Leffler, 2009).…”
Section: Les Finalités De L'éducation Entrepreneurialeunclassified
“…Le principal obstacle se situe cependant, à l'instar des notions d'entrepreneuriat et de « culture entrepreneuriale », au niveau de la difficulté de définir les termes utilisés pour parler d'entrepreneuriat en milieu scolaire. Dans les écrits anglophones, ce vocabulaire se cristallise autour de deux principaux vocables, à savoir entrepreneurship education et enterprise education, auxquels on pourrait ajouter un troisième, soit small business education (Breen, 2004;Gorman, Hanlon & King, 1997). Si ces termes peuvent parfois être utilisés de manière interchangeable, nombre d'auteurs mettent pourtant en évidence la spécificité de chacun d'eux (Cummins & Dallat, 2004;Leffler, 2009).…”
Section: Les Finalités De L'éducation Entrepreneurialeunclassified
“…Recent research findings show that universities and their didactic activities can influence the students' decision-making process with respect to new venture creation (Béchard & Toulouse, 1998;Gorman et al, 1997;Hostager & Decker, 1999). Given a positive predisposition on the part of the students, training programs and the image of business founders within the university seem to have the potential to increase the propensity of graduates to found new businesses after leaving university (Autio, Keeley, Klofsten & Ulfstedt, 1997;Begley, Tan, Larasati, Rab, Zamora & Nanayakkara, 1997;Brown, 1990;McMullan, Long & Wilson, 1985).…”
Section: Education Programsmentioning
confidence: 99%
“…In controlled studies, it was shown that entrepreneurship courses help graduates make better decisions in the start-up process (Vesper & Gartner, 1997). Enhancing the students' understanding of the processes involved in the creation of a new business is therefore an important objective in entrepreneurship education (Gorman et al, 1997;Hills & Morris, 1998).…”
Section: Education Programsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, militates against societal problems by increasing employment (Nybakk & Hansen, 2008). Most studies have shown there is a positive relationship between entrepreneurship and economic growth in terms of job creation, firm survival and technological change (Gorman, et al 1997;Lena and Wong 2003;Karanassios, Pazarskis et al, 2006). It is seen as an engine of economic progress, job creation and social adjustment (Yosof, et al, 2007).…”
Section: Introductionmentioning
confidence: 99%